Global Risk Management in SARS (Severe Acute Respiratory Syndrome) - Yoon, Junghyun; Oh, Seunghee (Advances in Social Sciences Research Journal, 2017)
Humans in the twenty-first century are frequently experiencing transnational disasters. The Severe Acute Respiratory Syndrome(SARS), a classic case of global pandemic in 2003, resulting in 774 deaths among 8,096 infected people globally. Through the case of SARS in 2003, this article critically examine the explanations based on the existing national level of response capacity in regard to management of transnational pandemic, and then propose the interpretation of the supranational risk communication as an alternative framework. Although Singapore and Hong Kong were seriously affected by SARS in similar conditions, the former was able to surmount the crisis more successfully than Hong Kong. This will show that the active attempts of supranational risk communication have acted as an important variable. Furthermore, it could be that the differences in supranational risk communication between the two countries have stemmed from the differences in diplomatic autonomy and political leadership.